2020
DOI: 10.3390/nano10061124
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel 1T/2H-MoS2 from MoO3 Nanowires with Enhanced Photocatalytic Performance

Abstract: Metallic 1T-phase MoS2 is a newly emerging and attractive catalyst since it has more available active sites and high carrier mobility in comparison with its widely used counterpart of semiconducting 2H-MoS2. Herein, 1T/2H-MoS2(N) (N: MoO3 nanowires were used to prepare 1T/2H-MoS2) was synthesized by using molybdenum trioxide (MoO3) nanowires as the starting material and applied in the photodegradation of antibiotic residue in water. Enhanced photocatalytic performance was observed on the obtained 1T/2H-MoS2(N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…In contrast, 1T-MoS 2 @TNTs (0.5 wt %) can degrade 57% TC-HCl under the same conditions, which is higher than previously reported efficiencies of 15 and 25%. 9,14 In addition, Figure S4 shows the degradation curves of 1T-MoS 2 @TNTs with different loaded amounts of 1T-MoS 2 , where it is observed that the prepared 0.5 wt % 1T-MoS 2 @TNTs exhibits the highest catalytic activity. The pseudo-first-order kinetics fitting of the photo- degradation is given in Figure 6b.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, 1T-MoS 2 @TNTs (0.5 wt %) can degrade 57% TC-HCl under the same conditions, which is higher than previously reported efficiencies of 15 and 25%. 9,14 In addition, Figure S4 shows the degradation curves of 1T-MoS 2 @TNTs with different loaded amounts of 1T-MoS 2 , where it is observed that the prepared 0.5 wt % 1T-MoS 2 @TNTs exhibits the highest catalytic activity. The pseudo-first-order kinetics fitting of the photo- degradation is given in Figure 6b.…”
Section: mentioning
confidence: 99%
“…To date, considerable efforts have been made to optimize the MoS 2 nanocomposites and expand their practical use. For example, Zheng et al applied a hierarchical MoS 2 nanosheet on a TiO 2 nanotube (TNT) array to enhance the photocatalytic and photocurrent performance . Zhao et al used the MoS 2 quantum dots@TNTs composites to improve the visible-light-driven high-efficiency photocatalysis .…”
Section: Introductionmentioning
confidence: 99%
“…Most crystals (e.g., TiO 2 [262] , [263] , [264] , [265] , [266] , [267] , [268] , [269] , [270] , CdS [271] , Bi 2 O 3 [272] , MoS 2 [273] and ZnIn 2 S 4 [274] ) have many different natural or artificial phases. The construction of the phase junction is a significant approach to improve the photocatalytic performance through accelerating the migration of electrons and holes.…”
Section: Strategies For Photocatalytic Activity Improvementmentioning
confidence: 99%
“…Among the solid catalysts studied, molybdenum trioxide and materials based on the transition metal Mo, have been the focus of several technological applications, mainly due to their structural characteristics, as photocatalysts, 9,13 gas sensors, 14 battery applications, 5,15,16 and for biodiesel production. 10,12,17,18 Also, their selectivity and high catalytic activity are primarily related to Lewis and Brønsted-Lowry acidity.…”
Section: Introductionmentioning
confidence: 99%